Food Security Analysis of Melon Farmer Households During the Covid-19 Pandemic in Tuban Regency - Nuhfil Hanani; Rika Asterina; Siti Nur Komala Sari; Fahriyah Fahriyah; Condro Puspo Nugroho (Agriekonomika, 2023)
The impact of the coronavirus entering Indonesia is felt by various parties, including farmer households. In addition to the obligation of farmers to supply food for the entire community, they are also pressured to pay attention to the nutritional intake of their households. High-nutrition food is needed during the COVID-19 pandemic to maintain immunity, but it is difficult to fulfill during the pandemic due to the increasing prices of food. If production and sales of agricultural products decrease, the ability of households to consume food that is suitable in quantity and quality will also decrease. However, the agricultural sector in Indonesia shows positive growth. This study aimed to determine the household food security of melon farmers based on 1) food quantity, from EAR and PAR results, and 2) food quality, from Desirable Dietary Pattern scores. Determination of the research location purposively. Food consumption data were obtained from food recall. The results of the analysis based on the quantity aspect showed that the average actual energy consumption was 1,854.78 kcal/capita/day (88.3%), while protein consumption was 68.47 grams/capita/day (120.1%). The results of the analysis of the quality of food consumption are 81.5, it can be seen that the household food consumption of melon farmers from the aspect of quantity and quality has not been achieved.